(untitled) (Research, Society and Development, 2022)
The expansion of the telecommunications sector in Brazil in recent years and the consequent increase in demand for telecommunication towers open space for a discussion about the guidelines to be taken during the execution of projects of this type of structure. Because they are light and slender structures, wind loads become preponderant for the design of these towers and wind analysis is an important topic to be discussed. Thus, this work analyzes design aspects employing numerical modeling and parametric studies. The Brazilian standard NBR 6123:1988 was used to obtain the wind speed and its static and dynamic loads, to compare the responses generated by each of the methods. Then, this process was repeated following the European standard IEC 60826:2017, to compare the results between the two standards methods. A parametric study was also performed with towers of different heights to better understand the structure behavior. The tower responses were obtained using the finite element software SAP2000, in which a lattice tower model with a constant square section was developed, to which the wind loads calculated according to the aforementioned standards were applied. The results showed that each analysis method generates considerably different results, revealing that this is a point that should be very well studied during the design of telecommunication towers.